Analysis of retail marketing mix as a driver of hypermarket customer loyalty (a review of Carrefour and Giant hypermarkets) - Nisya Nabila Priorinta (Indonesia Auditing Research Journal, 2021)
This research studies about the effects of retail marketing mix to loyalty behavior that is measured by visitor frequency in Carreefour and Giant Hypermarkets. Six dimensions of retail marketing mix are place, atmosphere, merchandise, promotion, price and service. This study used multiple regression analysis to indicate that there are positive and significant influence and dominance between factors retail marketing mix to visitor frequency, independent sample t-test to indicate that there are differences in worker performance between Hypermarket Carrefour and Giant, and one sample t- test to indicate that costumers perception with Hypermarkets' performance. Data were obtained by distributing questionnaires to 137 respondents from Carrefour and Giant visitors. The results of this study show that there are positive and significant influences between the two factors of retail marketing mix to visitor frequency and the dominance factor is atmosphere, there are performance differences between Carrefour and Giant where Carrefour's performance is better than Giant, but Carrefour and Giant have a good performance in consumer perception.